When Julia danced bomba = Cuando Julia bailaba bomba [book with audioplayer] - Ortiz, Raquel M. ([Library Ideas, LLC], 2022)
"Julia, they're already warming up. Hurry!" Cheito says to his little sister as they rush to their bomba class. Cheito is a natural on the drums, but Julia isn't as enthusiastic about dancing. Julia tries to imitate the best dancer in the class, but her turns are still too slow, her steps too big. She just can't do anything right! When the instructor announces the younger students will be participating in the bombazo and performing a solo, Julia is terrified. When it's her turn, she takes a deep breath, closes her eyes and focuses on the beat of the drum. As she dances, Julia notices that the drums are actually talking to her. Feeling braver, she stops worrying and trying so hard. Instead, she loses herself in the rhythm of the bomba drums and enjoys herself! Introducing children to the Afro-Latino tradition of bomba music and dancing, author and educator Raquel M. Ortiz shares another story for children ages 5-9 about her rich Puerto Rican heritage. With lively illustrations by Flor de Vita that aptly express Julia's frustration, fear and joy, this book will help children understand that practicing yields results!